STAT3-orchestrated gene expression signatures and tumor microenvironment in esophageal squamous cell carcinoma uncovered by single-cell sequencing - Pang, Shilian; Chen, Yurao; Zheng, Zemao; Wang, Luoshai; Chen, Ronghuai; He, Ming; Zhao, Xiang; Yao, Juan; Jin, Liyan (Biochimica et biophysica acta. General subjects, 2025)
The progression of Esophageal Squamous Cell Carcinoma (ESCC) can be dissected with greater precision using multi-omics and single-cell RNA sequencing (scRNA-seq) compared to traditional methodologies. These advanced approaches enable a comprehensive understanding of cellular heterogeneity and molecular dynamics, offering higher resolution insights into cancer development. Moreover, analyzing transcription factor regulatory networks provides innovative avenues for identifying cancer biomarkers and therapeutic targets, driving new perspectives in cancer research. To explore the molecular mechanisms and cellular dynamics of ESCC. Utilizing bulk-RNA-seq and single-cell transcriptomics, our study identify major cell types, transcriptomic gene and function changes during ESCC progression. Validation experiments in clinical sample tissues and ESCC cell lines to confirm core regulation factor in ESCC. We identified six major cell types in the ESCC scRNA-seq dataset and revealed profound shifts in cellular composition and transcriptional profiles. Notably, STAT3 was found to be a core regulator in ESCC and negatively regulated LHPP expression at promoter sites. Elevated STAT3 and reduced LHPP expression were consistently observed in patient samples, highlighting their inverse relationship in ESCC pathogenesis. This study integrates bulk-seq and scRNA-seq data to reveal the pivotal role of STAT3 in ESCC. STAT3 negatively regulates LHPP expression, driving tumor progression. These findings underscore the therapeutic potential of targeting STAT3 in ESCC. Key words: ESCC, single-cell transcriptomics, ESCC microenvironment, STAT3. [Display omitted] •Integrative Transcriptomics Approach: The study combines bulk RNA-seq and single-cell transcriptomics to achieve a high-resolution understanding of ESCC progression, identifying key cellular and molecular dynamics within the tumor microenvironment.•STAT3 as a Core Regulator: STAT3 was identified as a pivotal transcription factor in ESCC, with evidence supporting its upregulation and role in driving oncogenic pathways.•Clinical Relevance and Validation: Elevated STAT3 and reduced LHPP expression were consistently validated in clinical samples, underscoring their potential as biomarkers and therapeutic targets for ESCC.